First record of Platyscapa quadraticeps (Hymenoptera: Chalcidoidea: Agaoninae) in Colombia : A warning sign?. (2019)
The first occurrence record of Platyscapa quadraticeps in Colombia is reported. This wasp is the pollinator of Ficus religiosa, a tree species introduced mainly for ornamental use. The obligate mutualistic relationship between them could result in the naturalization of both species, with possible negative consequences.